Relation between coumarate decarboxylase and vinylphenol reductase activity with regard to the production of volatile phenols by native Dekkera bruxellensis strains under ‘wine-like’ conditions - Sturm, Maria Elena; Assof, Mariela Vanesa; Fanzone, Martín Leandro; Martínez, Claudio; Ganga, M. Angélica; Jofre, Viviana Patricia; Ramirez, María Laura; Combina, Mariana (2018)
Dekkera/Brettanomyces bruxellensis is considered a major cause of wine spoilage, and 4-ethylphenol and 4-ethylguaiacol are the most abundant off-aromas produced by this species. They are produced by decarboxylation of the corresponding hydroxycinnamic acids (HCAs), followed by a reduction of the intermediate 4-vinylphenols. The aim of the present study was to examine coumarate decarboxylase (CD) and vinylphenol reductase (VR) enzyme activities in 5 native D. bruxellensis strains and determine their relation with the production of ethylphenols under ‘wine-like’ conditions. In addition, biomass, cell culturability, carbon source utilization and organic acids were monitored during 60 days. All strains assayed turned out to have both enzyme activities. No significant differences were found in CD activity, whilst VR activity was variable among the strains. Growth of D. bruxellensis under ‘wine-like’ conditions showed two growth phases. Sugars were completely consumed during the first growth phase. Transformation of HCAs into ethylphenols also occurred during active growth of the yeast. No statistical differences were observed in volatile phenol levels produced by the strains growing under ‘wine-like’ conditions, independently of the enzyme activity previously recorded. Furthermore, our results demonstrate a relationship between the physiological state of D. bruxellensis and its ability to produce ethylphenols. Inhibition of growth of D. bruxellensis in wine seems to be the most efficient way to avoid ethylphenol production and the consequent loss of wine quality.